Efektivitas Metode Diskusi Kelompok terhadap Peningkatan Partisipasi Aktif Siswa pada Materi Hak dan Kewajiban dalam Pembelajaran PPKn di Sekolah Dasar - Fitri Noviani; Ibnu Muthi (Lembag, 2025)
This study aims to analyze the effectiveness of the group discussion method in increasing students' active participation in the material on rights and obligations in learning Pancasila and Citizenship Education (PPKn) in Elementary Schools. The problem underlying this study is the low student participation due to conventional learning methods that tend to be one-way and less actively involve students. The group discussion method was chosen as an alternative interactive and participatory learning method because it allows students to dialogue, express opinions, and work together to solve problems. This study uses a qualitative approach with a literature review method (library research). Data sources come from scientific journal articles, reference books, and previous research that is relevant in the last 5-10 years. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that the group discussion method is effective in increasing student involvement cognitively, affectively, and psychomotorically. In addition, this method also supports the development of student character such as democratic attitudes, responsibility, and tolerance. Therefore, the application of group discussions is highly recommended as a PPKn learning strategy that can create a meaningful and enjoyable learning atmosphere at the elementary school level.